Court management in transformation China: A Perspective Of Civil Justice. (2nd January 2018) - Fu, Yulin
Abstract : In China, "judicial management" mainly includes case management, case management, judiciary personnel management and judicial property management. As a basic concept, "judicial independence" means the courts exercising judicial power independently as a whole, instead of independence of a single judge or collegiate bench as to manage the cases. Such a system has been criticized as "bureaucratization of adjudication" in that the leaders or managers of the courts actually share the judges' judicial power so as to damage both transparency and efficiency of judicial processes. A series of reforms aim to establish a new mechanism as so called "panel responsibility" or "trial accountability" system, which will adjust the relationship among the judges or penal as a case manager and their leaders as a judge manager under the principle "Let the trier/ inquisitor to decide, and let the decider to be responsible".